On-Farm Demonstration of Soil Water Movement in Vegetables Grown with Plasticulture - Eric H. Simonne; David W. Studstill; Robert C. Hochmuth; J. T. Jones; C. W. Starling (EDIS)
The goals of this project were to demonstrate to cooperating growers how irrigation and fertilizer management are linked together and how management may prevent water movement below the root zone. More specifically, the objectives were to: establish partnerships with three key growers and discuss fertilizer and irrigation management, determine the position of the water front throughout the growing season, diagnose crop nutritional status, and determine nitrate distribution in the soil profile at the end of the growing season. This document is HS1008, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2005.